Enterprise Risk Management as a Catalyst for Strategic Governance, Risk, and Compliance (GRC) Alignment in IT Companies - Kumar, Karan (Digital Repository of Theses, 2025)
Enterprise Risk Management (ERM) is increasingly recognized as a strategic mechanism for fostering alignment among IT companies' Governance, Risk, and Compliance (GRC) functions. Such alignment enables companies to respond effectively to dynamic risk landscapes and regulatory demands while supporting resilience and strategic flexibility. This study examines ERM as a catalyst for GRC alignment, focusing on the role of stakeholder influence, the effectiveness of alignment strategies, the utility of assessment tools, and the barriers encountered in achieving cohesive ERM-GRC integration. The role of key stakeholders, including board members, senior management, and regulatory bodies, is pivotal in shaping the priorities and approaches within ERM-GRC alignment processes. Their influence is not limited to setting alignment objectives, but also extends to actively shaping the success of strategic initiatives aimed at achieving coherence across governance, risk, and compliance domains. The study delves into the influence of these stakeholders, revealing that their engagement is a fundamental component of successful ERM-GRC alignment. To evaluate alignment progress, the study also assesses the tools and techniques employed by IT companies, such as automated GRC platforms, data analytics tools, and real-time risk monitoring systems. The effective use of these tools provides organizations with valuable insights into alignment status, helping them identify gaps, mitigate potential risks, and refine their approaches. However, the research identifies various challenges that hinder alignment efforts, including the complexity of integrating diverse compliance requirements, resource constraints, and the evolving nature of regulatory standards. Quantitative analysis highlights that these challenges are particularly pronounced in rapidly evolving IT environments, where agility and adaptability are essential. Overall, this study demonstrates that successful ERM-GRC alignment in IT companies depends heavily on stakeholder engagement, strategic adaptability, and the strategic selection of assessment tools. By addressing identified challenges, IT companies can leverage ERM to enhance governance, manage risks proactively, and maintain compliance more effectively, ultimately supporting organizational resilience and long-term strategic growth. Key words: Enterprise Risk Management, ERM, Catalyst, Strategic Governance, Risk, Compliance, GRC, GRC Alignment, IT Companies, Challenges in ERM-GRC Alignment